Idiopathic eosinophilic enteritis in a pet goat. Issue 1 (14th May 2014) - Groenevelt, Margit; Busschers, Evita; Fews, Debra; Grogono‐Thomas, Rose
Abstract : A young goat referred to Langford Veterinary Services presented with chronic diarrhoea and weight loss with good appetite. Previous treatment with anthelmintics, coccidiostats and two courses of antibiotics had not resulted in improvement. On clinical examination, no abnormalities were detected except diarrhoea. Haematology revealed an elevated white blood cell count; biochemistry, faecal egg counts and an abdominal ultrasound revealed no abnormalities. A course of trimethoprim‐sulfadiazine and meloxicam was started for a suspected chronic intestinal inflammation. Twelve days after start of treatment, the goat presented with lethargy, inappetance and abdominal pain. Abdominal radiographs revealed distended large intestines with free fluid in the abdomen. An exploratory laparotomy was performed. Small quantities of fibrin around the colon were detected. Histological biopsies taken from the mid jejunum, caecum and colon revealed severe eosinophilic enteritis and typhlitis and a mild eosinophilic colitis. On the first day of immunosuppressive treatment, the animal deteriorated and was euthanised.